2003
DOI: 10.1007/s00122-003-1354-5
|View full text |Cite
|
Sign up to set email alerts
|

AFLP analysis of genetic relationships among aromatic grapevines (Vitis vinifera)

Abstract: Genotypic diversity has been detected among aromatic grapevines (Vitis vinifera) by molecular markers (AFLPs). The 22 primer-pairs generated a total of 1,331 bands of which 564 (40%) were polymorphic over all the genotypes. The bootstrap analysis pointed out that a large number of polymorphic bands (200-400) has to be used for a better estimation of the genetic distances among genotypes; 383 polymorphic AFLP bands were used for the cluster and the principal coordinate analyses because they did not present miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Different PCR-based molecular markers have been used for the comparison of grapevine genotypes, including RAPD and ISSR systems (Herrera et al 2002), microsatellites (Thomas and Scott 1993;Bowers et al 1996;Sefc et al 1999) and AFLPs (Cervera et al 1998;Fanizza et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different PCR-based molecular markers have been used for the comparison of grapevine genotypes, including RAPD and ISSR systems (Herrera et al 2002), microsatellites (Thomas and Scott 1993;Bowers et al 1996;Sefc et al 1999) and AFLPs (Cervera et al 1998;Fanizza et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The coefficient of variation (CV) trend from five to 120 polymorphic bands was evaluated on Nei coefficient matrices for SSR markers and on dissimilarity coefficient (1-SM) matrices (Fanizza et al 2003) for multilocus markers. For each molecular marker system the CV trend was calculated three times on three independent sets of 1,000 bootstrap analyses performed with the Phylip package (Felsenstein 1989) on three randomised matrices of presence/absence.…”
Section: Gret1mentioning
confidence: 99%
“…Other molecular markers have been applied to characterize grapevine varieties such as inter-simple sequence repeat (ISSR), randomly amplified polymorphic DNA, amplified fragment length polymorphism, and chloroplastidial microsatellites, among others (Benjak et al 2005;Cunha et al 2009;Fanizza et al 2003;Herrera et al 2002;Moreno et al 1998). ISSR markers are frequently used on genetic diversity, phylogeny, gene tagging, genome mapping, and evolutionary biology studies (Godwin et al 1997;Gupta et al 1994;Reddy et al 2002;Zietkiewicz et al 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Different sets of molecular markers were used in studies on the identification of grapevine varieties [77,[113][114][115][116]. It is reported that the selection of a set of few SSR markers can be used to discriminate successfully V. vinifera L. varieties and to trace the row material used to produce the must [33].…”
Section: Plantmentioning
confidence: 99%